Methods of food grade nanoemulsion formulation, fabrication, and characterization - Elgharbawy, Amal A.M.; Mohd. Salleh, Hamzah (Elsevier, 2022)
Nanotechnology has sparked interest in distributing medications and lipophilic compounds, including fatty acids, colors, and tastes, in a variety of industries, mostly those related to food and pharmaceuticals such as antimicrobial agents in drug delivery and transporters. Nanoemulsions (NEs) have been studied for many years. NEs are nonequilibrium structures that are either oil in water (O/W) or water in oil (W/O) emulsions in the nanoscale with droplet widths ranging from 20 to 200 nm. They have high stability and are translucent or transparent, so they are widely used in various applications. Nanoemulsions offer enormous potential to improve the consistency and unique properties of traditional emulsions in a wide range of applications. Designing circumstances for stabilizing and choosing the NE's characteristic process would aid in its widespread and high-throughput manufacturing application in the food business, depending on their specific demands. To improve the solubility, bioavailability, and functionality of nonpolar active chemicals, one of the most promising systems to be examined is NEs. They are also excellent vehicles for the delivery of active compounds and nutraceuticals. This chapter focuses on the composition of NEs, methods of formulation, characteristics of NEs, and examples of their applications in food technology.